(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract. The leading cause of death in elderly patients currently remains heart disease, in particular acute coronary syndrome (ACS). Recently, revascularization therapy centers have been opened in almost all regions of our country. In particular, percutaneous coronary interventions (PCI) are carried out effectively to manage patients with ACS to improve the quality of life . These so-called endovascular interventions are currently a highly effective treatment method that can significantly improve the condition of patients and increase their tolerance to physical activity, returning people to normal everyday life.